Transaction Issues in Mobile Distributed Real-Time Database Systems - Singh, Prakash K.; Shanker, Udai (Recent Advances in Computer Science and Communications, 2021)
In recent years, a large number of populations are dependent on mobile database technology and it is difficult for us to imagine our lifestyle in absence of database. Today’s portable handy mobile devices take part in emerging new technology for sharing distributed applications or/ and information between many users even on the move (from one network to another). To manage this resulting large Volume of data in a wireless environment with time constraints such as deadline making it the fertile land of research for researchers. Fast transaction processing in many industrial applications is needed efficient algorithm and protocols in the field of mobile distributed real-time database (MDRTDBS). Transaction execution in a mobile environment has various interesting research issues like low bandwidth, storage capacity, power backup, priority scheduling policy, and concurrency and commits protocols, security, check-pointing etc. At first in our paper, we address performance issues that are important to MDRTDBS and then survey the various researches that have been done so far. In fact, this paper provides ground knowledge for addressing the performance issues important for mobile distributed real-time database and somehow helping to find out the future area of research in the field of MDRTDBS.
Keywords: concurrency control